2010
DOI: 10.1002/gcc.20746
|View full text |Cite
|
Sign up to set email alerts
|

A catalog of genes homozygously deleted in human lung cancer and the candidacy of PTPRD as a tumor suppressor gene

Abstract: A total of 176 genes homozygously deleted in human lung cancer were identified by DNA array-based whole genome scanning of 52 lung cancer cell lines and subsequent genomic PCR in 74 cell lines, including the 52 cell lines scanned. One or more exons of these genes were homozygously deleted in one (1%) to 20 (27%) cell lines. These genes included known tumor suppressor genes, e.g., CDKN2A/p16, RB1, and SMAD4, and candidate tumor suppressor genes whose hemizygous or homozygous deletions were reported in several t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 50 publications
3
79
0
Order By: Relevance
“…The low-density lipoprotein receptor-related protein gene (LRP1B) originally isolated on the basis of homozygous deletions detected in human lung cancer cell lines (Liu et al, 2000a(Liu et al, , 2000bKohno et al, 2010) was recently reported among the top 10 most significantly deleted genes across 3312 human cancer specimens (Beroukhim et al, 2010). LRP1B encodes for a member of the endocytic low-density lipoprotein receptor superfamily.…”
Section: Introductionmentioning
confidence: 99%
“…The low-density lipoprotein receptor-related protein gene (LRP1B) originally isolated on the basis of homozygous deletions detected in human lung cancer cell lines (Liu et al, 2000a(Liu et al, , 2000bKohno et al, 2010) was recently reported among the top 10 most significantly deleted genes across 3312 human cancer specimens (Beroukhim et al, 2010). LRP1B encodes for a member of the endocytic low-density lipoprotein receptor superfamily.…”
Section: Introductionmentioning
confidence: 99%
“…Homozygous deletion of PTPRD has been reported at a frequency of 8-20% in lung cancer, melanoma, neuroblastoma, glioblastoma multiforme, laryngeal SCC and lymphoma. [13][14][15][16][17][18][19] Mutations of the coding exons of PTPRD and methylation at the promoter region have also been reported in lung cancer, melanoma, glioblastoma, breast and colorectal cancers, indicating that multiple mechanisms of disruption affect this gene in cancer. 17,[20][21][22] The overexpression of PTPRD in vitro causes transient growth arrest and an increase in apoptotic cells, with the converse demonstrated for the knockdown of PTPRD.…”
mentioning
confidence: 99%
“…This result might indicate that the ability of Nrf2 protein to degrade under homeostatic conditions varies among different cell lines. Several reports indicated a relationship between Keap1 mutation and poor prognosis or chemoresistance in NSCLC cell lines and tumors (31)(32)(33). Keap1 mutations are present in a series of NSCLC cell lines that were used in this study (Supplementary Table S1).…”
Section: Discussionmentioning
confidence: 91%